Trace Element Contents in Thyroid of Patients with Diagnosed Nodular Goiter Investigated by Instrumental Neutron Activation Analysis - Zaichick, Vladimir (Jour Med Resh and Health Sci, 2021)
Background: Nodular goiter (NG) is an internationally important health problem. Objectives: The aim of this exploratory study was to examine the content of ten trace elements (TE): silver (Ag), cobalt (Co), chromium (Cr), iron (Fe), mercury (Hg), rubidium (Rb), antimony (Sb), scandium (Sc), selenium (Se), and zinc (Zn) in the normal thyroid and in the thyroid tissues with diagnosed colloid NG. Methods: Thyroid tissue levels of TE were prospectively evaluated in 46 patients with NG and 105 healthy inhabitants. Measurements were performed using non-destructive instrumental neutron activation analysis with high resolution spectrometry of long-lived radionuclides. Tissue samples were divided into two portions. One was used for morphological study while the other was intended for TE analysis. Results: It was found that contents of Ag, Co, Cr, Fe, Hg, Sc, and Zn were significantly higher in goitrous thyroid than in normal gland. Conclusions: There are considerable changes in TE contents in the goitrous transformed tissue of thyroid.